ANTIMICROBIAL EFFECT OF TURMERIC OIL (CURCUMA LONGAL.) - Kim Cuc, Nguyen Thi; Kim Dung, Tran Thi; Cuong, Pham Viet (Vietnam Journal of Science and Technology, 2012)
Essential oil was extracted from turmeric rhizome by steam distillation and it’s composition was determined by GC-MS method. In total, 36 volatile compounds were identified and 13 of them had ≥90% identity with reference compounds. The main constituent of obtained turmeric oil was ar-turmerone (30.33%), followed by alpha-turmerone (14.14%). The antimicrobial activity of turmeric oil was evaluated by observing microbial growth on solid medium supplementing with different concentration of oil. The result showed that Gram positive bacteria were more sensitive to the oil than Gram (-) bacteria. B. cereuswas inhibited at 1%, while L. damsellalost it’s growth at essential oil concentration 3%only. The test-fungi exhibit different sensitivity to turmeric oil. The most resistant was MNh14 (Aspergillus sydowi) and MNh19 (Aspergillus japonicus) isolated from Litchi chinensis, these strains can tolerate 4% of oil in growth medium. Considering the importance of essential oils as ecofriendly agents, and their antimicrobial activity, the essential oils have potential as environmentally safe alternatives and as components in integrated pest management programs. Keywords. Curcuma longa, hydrodistillation, microbial activity, essential oil, turmeric rhizome.